Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1007/bf03043035
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the seasonality of North Sea zooplankton

Abstract: Frankfurt a. M.]Phenology and seasonality of the population response patterns of marine zooplankton provide a measure of the impact of climatic forcing upon the ecosystem, as most metazoans in the sea are periodically planktonic, usually in their pr0pagative phase. The global warming expectancy suggests intensified consideration of this aspect of ecosystem research. On the basis of the "Helgoland Roads zooplankton" time-series, such population specific investigations have been carried out. They suggest that te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 8 publications
3
29
0
Order By: Relevance
“…Larvae of the sea urchin Echinocardium cordatum (Kirby et al 2007), as well as of many decapod crustacean larvae (Lindley et al 1993), were found in the plankton in higher abundances and/or earlier due to temperature-induced shifts in the reproduction cycle. This is supported by Greve et al (2001), who found that temperature modifies the beginning, end, length and intensity of the seasonality of zooplankton populations (including meroplankton). Dippner (1997a,b) found that climate variability delays the spawning time of fish by up to 2 mo in near-coastal areas, and that recruitment variability of western mackerel and the 3 gadoids (North Sea cod, saithe and whiting) was highly correlated with the variability of North Sea SSTs.…”
Section: Recovery After the Severe Wintermentioning
confidence: 60%
“…Larvae of the sea urchin Echinocardium cordatum (Kirby et al 2007), as well as of many decapod crustacean larvae (Lindley et al 1993), were found in the plankton in higher abundances and/or earlier due to temperature-induced shifts in the reproduction cycle. This is supported by Greve et al (2001), who found that temperature modifies the beginning, end, length and intensity of the seasonality of zooplankton populations (including meroplankton). Dippner (1997a,b) found that climate variability delays the spawning time of fish by up to 2 mo in near-coastal areas, and that recruitment variability of western mackerel and the 3 gadoids (North Sea cod, saithe and whiting) was highly correlated with the variability of North Sea SSTs.…”
Section: Recovery After the Severe Wintermentioning
confidence: 60%
“…As noted above, Mackas et al (1998) estimated seasonal timing of N. plumchrus during the weathership time series using a combination of the biomass (all years) and stage composition (1971,1973,1980) indices, and concluded (based on those years of overlap) that peak biomass corresponded to a C5:total copepodites ratio between 35 and 65%. In this paper, we applied an additional phenology index based on cumulative integration of the biomass time series (developed by Greve et al 2001Greve et al , 2005, and described below) to examine interannual variation in cohort width (i.e. the duration of the period of high biomass).…”
Section: Methodsmentioning
confidence: 99%
“…Estimation of cohort width: Greve and colleagues have developed and applied an alternative method for indexing zooplankton seasonal phenology (examples in Greve et al 2001and Valdés et al 2006) that relies on cumulative integration through each year of the bell-shaped curve of abundance versus date or biomass versus date. 'Start-of-season' is defined as the date at which the cumulative curve crosses a lower threshold (15th or 25th percentile), 'middle-of-season' as the date for the 50th percentile, and 'end-of-season' as the 75th or 85th percentile.…”
Section: Analysis Estimation Of Peak Biomassmentioning
confidence: 99%
“…Notable among the changes in the North Sea meroplankton taxa are increases in the relative and absolute abundance of the larvae of benthic echinoderms (Lindley & Batten 2002) and an advance by 47 d, over 45 yr, in their timing of peak occurrence; this represents the largest phenological change detected in the plankton of this region so far (Greve et al 2001, Edwards & Richardson 2004. To determine which echinoderm species are involved in the increase in the meroplankton we sampled echinoderm larvae at the time of their peak abundance in June and July 2004 from CPR towroutes between 53 and 58°N, and 0 and 7°E (Kirby & Lindley 2005).…”
Section: Introductionmentioning
confidence: 99%